Evaluation of spatio-temporal water quality status of Jeera river, Odisha, India - Aiswarya Pati; Showkat Ahmad Mir; Archana Padhiary; Iswar Baitharu; Binata Nayak (Discover Water)
Abstract Jeera River of Bargarh District, Odisha faces serious deterioration due to massive human intervention. It is particularly susceptible to degradation because it receives industrial and waste water emissions from surrounding organizations and municipal bodies. The river was formerly a flourishing tributary of the massive Mahanadi River that possessed excellent navigability, an array of aquatic ecosystems, and a well-established basin with an expanding agricultural sector. The current condition of the Jeera River is deplorable, leaving behind only minimal economic and ecological values. The study emphasizes analyzing the seasonal variation of the water quality rating of Jeera River in terms of the Water Quality Index (WQI). WAWQI (Weighed Arithmetic Water Quality Index) values show that almost all sampling sites have poor or unsuitable quality. During the monsoon season, the water quality deteriorated the most, with an average WQI score of 516.430 compared to pre- and post-monsoon with average WQI values of 154.558 and 276.014 respectively. CCMEWQI (Canadian Council of Ministers of Environment Water Quality Index) values indicate that water quality ranges from marginal, and poor to fair. This study concludes that out of the eight sampling sites, station 5 (Dumerpali) is observed to be the most polluted site. Many water quality parameters including iron, turbidity, nitrate, phosphate, E. coli, and Total coliform are found to exceed the permissible limits prescribed by WHO and BIS. Reducing sewage outflow, blocking direct stormwater discharge, and avoiding continuous solid garbage disposal by neighbouring populations are ways to improve river water quality. Graphical abstract